A Local Budget Transparency Index for Cameroon's Local Councils : Insights from a Benchmarking Exercise - Alton, Martin Luis; Agarwal, Sanjay; Songwe, Vera (World Bank, Washington, DC, 2014)
Transparent budgets and public financial management processes constitute a key pillar of good governance. However, while this has been increasingly recognized for national budgets, little attention is paid to subnational budget transparency. To fill this lacuna, a World Bank-supported initiative piloted a local budget transparency index (LBTI) in two of Cameroon s ten regions. Thirty-one local councils in the Northwest Region and nineteen in the Adamawa Region self-assessed the openness of their budget processes by filling out questionnaires in 2012. The councils were then ranked, the results were published, and, in Adamawa, discussed in a public meeting called by the region s governor and attended by mayors and the media. Through this exercise, mayors of low-ranking councils were publicly questioned about their low scores, which led to a palpable desire on their part to better perform in the next round of the survey. In 2013, independent nongovernmental organizations (NGOs) gathered the same information in a second round of surveys. This note discusses the methodology, main findings, and results from the LBTI pilot in the two regions and concludes with key challenges and lessons learned.